ANALISIS KEBUTUHAN PENGEMBANGAN E-LEARNING FISIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN MINAT BELAJAR SISWA - Pratiwi, Juli; Rahmad, M.; Syahril, Syahril (STKIP PGRI Situbondo, 2025)
The independent curriculum was developed as a more flexible curriculum framework, centered on basic material and developing students' uniqueness and abilities. One way that can be used to develop students' abilities is through learning media that is in accordance with student characteristics. This study aims to analyze students' interest in using learning media in the form of e-learning in physics learning. The research methodology used is a qualitative method using data collection techniques through teacher interviews and student response questionnaires. The objects of the study were several high schools in North Sumatra and Pekanbaru and a sample of 81 students. Based on the results of the student response questionnaire, 92.6% of students were interested in learning using e-learning, and 100% of students already had cellphones so that they supported the development of E-learning learning media. E-learning is one of the innovations in the field of education in the form of a learning system carried out through electronic media, such as computers, tablets, or smartphones that can be accessed without time and distance limits.